2018
DOI: 10.3390/su10072358
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness and Its Relationship with the Concept of the Living Being: A Longitudinal Study

Abstract: Abstract:There is currently a growing theoretical discussion about the foundations that underlie the development of environmental awareness and nature care in early childhood. The aim of this study is to analyze how the environmental concerns of young children emerge and evolve during early childhood and whether these concerns are connected to an understanding of the biological notion of the living being. This study is designed to address methodological limitations of previous studies through a longitudinal ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(56 reference statements)
0
1
0
2
Order By: Relevance
“…Apoyando estas ideas, Villanueva et al (2018) mencionan que el estado ético único que los niños pequeños parecen atribuir a la vida vegetal puede surgir inicialmente en la primera infancia y, lo que es más importante, independientemente de su evolución conceptual en el biológico. De acuerdo con estas ideas, el pensamiento relacionado con la vida vegetal en la primera infancia se desarrolla independientemente de la comprensión inicial de la noción de ser vivo.…”
Section: El Concepto Ser Vivo Y El Mundo Vegetalunclassified
“…Apoyando estas ideas, Villanueva et al (2018) mencionan que el estado ético único que los niños pequeños parecen atribuir a la vida vegetal puede surgir inicialmente en la primera infancia y, lo que es más importante, independientemente de su evolución conceptual en el biológico. De acuerdo con estas ideas, el pensamiento relacionado con la vida vegetal en la primera infancia se desarrolla independientemente de la comprensión inicial de la noción de ser vivo.…”
Section: El Concepto Ser Vivo Y El Mundo Vegetalunclassified
“…Indeed, some literature has suggested that although it is usual to register growth in moral judgement as individuals grow old, education attainment would be a stronger predictor of the development of moral judgement than would mere chronological age, per se (Rest, 1994). Moreover, research has suggested that due to attendance to formal education, complex biological and morally rooted concepts and biocentric reasoning can be introduced earlier than shown in the developmental literature-around the Grades 2 and 5 of primary school (Severson & Kahn, 2010;Villanueva, Villarroel, & Antón, 2018).…”
Section: How Does Educational Attainment Influence Ec?mentioning
confidence: 99%
“…In "Ecological Security and the United Nations System", published in 1998, experts and scholars from various countries put forward views on the definition of ecological safety, the factors that lead to insecurity, the degree of risk, and the trend of change [16][17][18]. Humanity's understanding and awareness of ecological and environmental issues have gradually deepened, and the concern has steadily increased [19]. It has slowly progressed from concern for environmental problems to environmental safety to ecological security [20,21].…”
Section: Introductionmentioning
confidence: 99%